Memórias das mulheres mártires: modelos de resistência e liberdade - Siqueira, Silvia M. A. (Horizonte, 2006)
The aim of this article is to emphasize woman’s presence in Christian martyrs’ descriptions during the 2nd and 3rd centuries, making use of theoretical and methodological fundamentals of the history of women. It highlights their experiences and actions as active subjects in a specific historical context. The documentation refers to a considerable number of women who crossed social and religious barriers and confessed their option of faith in public. More than describing and recording woman’s participation, it analyzes and explains some situations with basis on the delimitation of specific aspects of the women’s life, including the remarkable presence of a symbolic universe. The most important document is the Passion of Perpetua and Felicitas, which deals with the arresting, condemnation and martyrdom of a group of men and women who had confessed and reaffirmed their Christian creeds. The fact took place in the city of Cartago, in North Africa, in the 3rd century. The document is considered an archetype of Christian martyrs’ acts and a documentary record of the two women. The analysis demonstrates the construction of models of resistance and freedom that characterize the depth of the feminine world at the time.